Self-regulation in University Students: Learning Strategies, Motivation and Emotions - Hendrie Kupczyszyn, Karina Noelia (2019)
The objective of this study was to analyze academic self-regulation among university students based on their learning strategies, emotions and motivational thoughts, attained through this quantitative, ex post facto study. The sample group included 83 first-year Psychology majors in the city of Corrientes, Argentina.  The students responded to questionnaires to assess student motivation and emotions before and after performing a specific task and to determine perceived learning strategies. A one-way ANOVA was conducted as well as a MANOVAS for data analysis based on the objectives, variables and its dimensions. Results reveal significant differences regarding student anxiety based on sex and age as well as  the amount of concentration required to perform a task, according to sex. Variances were also observed in the average scores for the task according to student information processing, that is, the subjective skill perceived to be required to perform the task and the emotion centered on student results. The importance of student self-regulation was observed which is consistent with the reviewed literature, leading to the attainment of goals via cognitive and emotional pathways. Future research recommendations include increasing the sample size as well as including other variables for a broader picture of the self-regulation process.